Altered Spatial and Temporal Brain Connectivity in the Salience Network of Sensorineural Hearing Loss and Tinnitus - Xu, Xiao-Min; Jiao, Yun; Tang, Tian-Yu; Lu, Chun-Qiang; Zhang, Jian; Salvi, Richard; Teng, Gao-Jun (Frontiers in Neuroscience, 2019)
Sensorineural hearing loss (SNHL), sometimes accompanied with tinnitus, is associated with dysfunctions within and outside the classical auditory pathway and the salience network, which anchored in bilateral anterior insula and dorsal anterior cingulate cortex, has been demonstrated in sensory integration. Partial auditory deprivation could alter characteristics of the salience network and other related brain areas, proving support for hearing impairments-induced neuropsychiatric symptoms. To test this hypothesis, we performed fMRI scanning and neuropsychological tests on 32 subjects with long-term bilateral hearing impairment and 30 well-matched Controls. Non-directional functional connectivity and directional Granger causality analysis were used to identify aberrant spatial and temporal patterns of connections targeting bilateral anterior insula and dorsal anterior cingulate cortex. We found that the left anterior insula showed decreased connectivity with right precentral gyrus and superior frontal gyrus. The connections between the dorsal anterior cingulate cortex and middle frontal gyrus, superior parietal gyrus and supplementary motor area were also reduced. Relative to Controls, SNHL patients showed abnormal effective connectivity of the salience network, including inferior temporal gyrus, cerebellum lobule VI, lobule VIII, precentral gyrus, middle frontal gyrus and supplementary motor area. Furthermore, correlation analysis demonstrated that some of these atypical connectivity were correlated with performance of neuropsychiatric tests. These findings suggest that the inefficient modulation of the salience network might help to better understand the neural basis of SNHL and tinnitus, as well as associated cognition and emotion deficits.